Sanctions For Moral Rights Violations in Law No. 28 Of 2014 Concerning Copyright - Amalia, Rafika (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The purpose of writing this article is to analyze the regulation of moral rights in Copyright Law no. 28 of 2014 and examines the regulation of sanctions for violations of moral rights. The research method used is normative legal research using a statutory approach and analysis of legal concepts. The results of this research are that the regulation of the protection of moral rights in copyright law is clearly regulated in Article 5. Furthermore, the regulation of sanctions in copyright law has not been regulated. Copyright law only regulates sanctions for violations of economic rights. In contrast to the previous copyright regulations in 2002, sanctions for violations of moral rights were stipulated, but these regulations are not included in the current copyright regulations.